Biology, Behavior, and Larval Morphology of Salbia lotanalis (Lepidoptera: Crambidae), a Potential Biological Control Agent of Miconia calvescens (Myrtales: Melastomataceae) from Costa Rica. (1st November 2014) - Castillo, Alexander; Johnson, M Tracy; Badenes-Pérez, Francisco R
Abstract: The leaf roller Salbia lotanalis Druce (Lepidoptera: Crambidae), a potential biological control agent of Miconia calvescens de Candolle (Melastomataceae), was studied in Costa Rica. Larvae were collected from a field site near San José and the insect was reared in the laboratory to study its biology and behavior. Chaetotaxy and morphology of final-instar larvae were described. Using head capsule width measurements, we determined five larval instars in S. lotanalis . The insect was easily reared in the laboratory on M. calvescens seedlings and the life cycle of the insect was completed in 71.3 and 66.4 d for females and males, respectively. Dissection of ovarioles indicated that females could lay>400 eggs. Larvae are initially gregarious, but become solitary as third instars. First- to fourth-instar larvae prefer to use leaf rolls already formed by other larvae, but fifth-instar larvae prefer to make a new leaf roll rather than using leaf rolls already made and occupied by other larvae. Pupation occurs in leaves, where prepupae build a pupation chamber. Host-specificity tests, including larval feeding tests and two-choice and no-choice oviposition experiments in the laboratory, indicate that S. lotanalis has a narrow host range restricted to Miconia spp. and other Melastomaceae. Levels of parasitism in the native habitat of S. lotanalis in Costa Rica were low. In locations like Hawaii, where there are no native Melastomataceae, S. lotanalis has the potential of being an effective biological control agent against M. calvescens, but interference from resident natural enemies of Lepidoptera could be high.